ANALYSIS OF POLITENESS CONVERSATION AMONG TEACHER AND STUDENT IN WHAT’S APP APPLICATION - Noviarini, Tiara; Yulianto (IJLECR (International Journal of Language Education and Cultural Review), 2019)
This study aims to find out the utterances in the conversation between teacher and students through the application message what’s an appand it is to find out the utterances which include positive politeness and negative politeness. This research is a qualitative descriptive study. The method used observation and note-taking techniques. The sources of data in this study were a teacherand student conversations weretaken through the messaging application What ’s an appfrom September to December 2018. The findings obtained that students’ politeness in conversation is not well placed. In addition, there were also found that students who seemed to dictate or schedule’s teachers. Although there are also polite student utterances, non-polite speeches are more of a nature of not knowing norms or manners. There ismuchnegative politeness than positive politeness. Keywords; Politeness, Utterance, Messages Application,What’sApp